Intime conviction’ in Germany: Conceptual Foundations, Historical Development and Current Meaning - Kai Ambos (Quaestio Facti, 2023)
The paper analyses the concept of «intime conviction» from the perspective of the German reformed inquisitorial criminal procedure. It starts off with the discussion of the foundations of the concept and explains how it – in essence, a flexible method to assess the available evidence – is integrated in the larger topic of the law of evidence, especially its production and evaluation (infra 1.). One key issue in this regard is how much freedom is given to the adjudicator to carry out the evidentiary evaluation and how this freedom relates to the applicable standard of proof (Beweismaßstab, estándar probatorio), being «beyond any reasonable doubt» (BARD) the most popular one. At any rate, in a (reformed) inquisitorial system all persons involved in the evidentiary process should be guided by the search for truth. To fully understand «intime conviction» and how it operates in the reformed inquisitorial procedure it is necessary to take a look at the historical development and the different factors influencing this development (2.). Here again the importance of the fact-finding authority (professional judges vs. laypersons, especially jury) comes to light and its dependence or at least relationship with the system of evidentiary evaluation. It will be seen that while the current system is based on the historical precedents the historical development has not been linear. This current system is then analysed in the following section (3.). It will be shown that it moves somewhere between the former system of legal proof and free evaluation. An expansive appeals jurisprudence has increasingly turned the «free conviction» into a sort of «conviction raisonnée», the lack of remaining (reasonable) doubts as a basis for a conviction makes clear that  it is the BARD standard which effectively informs the intime conviction method in substantive terms. The paper closes with some further considerations on the justification of the (high) standard and the (formally not necessary) proof of defences (4.).